PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN MENYEWA KENDARAAN YANG BERDAMPAK PADA KEPUASAN KONSUMEN PADA PT GUMILAR NUSA SEJATI DI JAKARTA SELATAN - Yusuf, Ade; Purnama, Aan; Kadarusman, Yuyus (LPPM University 17 Agustus 1945 Samarinda, 2025)
This study aims to determine the effect of price and service quality on the decision to rent a vehicle that has an impact on satisfaction at PT Gumilar Nusa Sejati, The statistical methods used are multiple linear regression analysis, correlation coefficient test, determination coefficient test, and t test and F test to test the hypothesis partially and simultaneously. The results of the study showed that price has a positive and significant effect on the decision to rent by 32% and the hypothesis test obtained a calculated t value> t table (6.793> 1.984). Service quality has a positive and significant effect on the decision to rent by 13.4% and the hypothesis test obtained a calculated t value> t table (3.898> 1.984). Price and service quality simultaneously have a positive and significant effect on the decision to rent by 40.1% and the hypothesis test obtained a calculated F value> F table (21.413> 2.700). The decision to rent has a positive and significant effect on customer satisfaction by 72.2%. The hypothesis test obtained a calculated t value> t table (15.968> 1.984). Keywords: price, service quality, rental decision, customer satisfaction